A Comparative analysis of the methods used for building Information / Content Centric Networks over Software defined networks - Vishnu Priya, B; JKR Sastry, Dr (International Journal of Engineering and Technology, 2018)
Ability to transfer huge amount of content to the target is the present-day requirements of the users which is not being used through internet-based protocol due to static nature of the internet. Software defined networks (SDN) provides the flexibility to implement any architecture as the control and data plane are separated. Information / content centric networks (ICN / CCN) can be implemented using SDN. The requirement of the massive delivery of the content can be archived through ICN/CCN.In this paper a comparative analysis of the methods used for building information centric networking ICN / CCN over software defined networks has been presented. The areas of research that needs to be undertaken further have also been cited in the paper. Â Â